A unique solution to improve an amblyopic child’s adherence to patching - Alharkan, Dora H. (International Journal of Research in Medical Sciences, 2019)
Amblyopia should be treated in early ages to have better outcomes. Stimulation of suppressed eye and depriving light stimulus to the good eye is the main principal of the amblyopia treatment. Adherence to the patching for the treatment of amblyopia in children remains challenging. This could be due to poor cooperation of child or ill-fitting patch. Younger children can be motivated to mimic cartoon figures to improve their adherence to patching. Amblyopia treatment is a team work of parents and optometrist who not only select the mode of management but improve the acceptance of child for patching. We present a child with mild anisometropia and hypermetropia-induced esotropia and amblyopia who was non-compliant to patching. An innovative idea by the parents using a Ninja Turtle patch on the prescribed spectacle was very well accepted by the child and both esotropia and amblyopia improved within four months of the patching treatment. The vision in the affected eye improved from 20/200 to 20/20 with refractive error correction and patching. We share this low-cost child-friendly patching technique that parents invented that can be used to improve adherence to patching by young children during amblyopia therapy. This parent’s innovation enabled to improve adherence and thus address amblyopia in patched eye and regain vision.